2018
DOI: 10.1007/s11481-018-9825-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of Macrophage Dopamine Receptors in Mediating Cytokine Production: Implications for Neuroinflammation in the Context of HIV-Associated Neurocognitive Disorders

Abstract: Despite the success of combination anti-retroviral therapy (cART), around 50% of HIV-infected individuals still display a variety of neuropathological and neurocognitive sequelae known as NeuroHIV. Current research suggests these effects are mediated by long-term changes in CNS function in response to chronic infection and inflammation, and not solely due to active viral replication. In the post-cART era, drug abuse is a major risk-factor for the development of NeuroHIV, and increases extracellular dopamine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 184 publications
(206 reference statements)
1
44
0
Order By: Relevance
“…D2-like DRs participate in a cAMP-independent pathway to regulate macrophage phagocytic function, thus reducing the secretion of IL-2, IL-4, and IFN-g (104), the effect of which is concentration-dependent. Studies demonstrated that D2-like DRs decrease the production of TNF-a, IL-6, and CCL2 at 10 −8 M concentration(105), while increase the production of IL-6 significantly at 2 and 20 × 10 −6 M (106) concentration.…”
mentioning
confidence: 99%
“…D2-like DRs participate in a cAMP-independent pathway to regulate macrophage phagocytic function, thus reducing the secretion of IL-2, IL-4, and IFN-g (104), the effect of which is concentration-dependent. Studies demonstrated that D2-like DRs decrease the production of TNF-a, IL-6, and CCL2 at 10 −8 M concentration(105), while increase the production of IL-6 significantly at 2 and 20 × 10 −6 M (106) concentration.…”
mentioning
confidence: 99%
“…Treatment with IL-10 (50 ng/mL) was used as a positive control, as this cytokine increases CCR5 expression in human monocytes, macrophages, and microglia (79,102,103). This use of a positive control in hMDM is similar to what we and others have published (50,60,104), as there is considerable variation in the hMDM inflammatory response to environmental stimuli (105-107). Therefore, donors in which IL-10 did not increase CCR5 at 1 hour were excluded from the analysis.…”
Section: Dopamine Alters the Proportion Of Ccr5 Conformations In Hmdmmentioning
confidence: 90%
“…These data suggest that individual variations in the response to dopamine could alter the effectiveness of MVC, changing the efficacy of antiretroviral therapy in HIV-infected substance abusers. As differences in dopamine receptor levels can contribute to donor-specific responses to dopamine (50), the donor responses to MVC and/or dopamine were compared to expression of all five subtypes of dopamine receptors (D1-like, DRD1 and DRD5; and D2-like, DRD2, 3, 4). These correlations were performed using expression of dopamine receptor transcripts by qPCR due to the lack of effective antibodies against human dopamine receptors and the inability of existing antibodies to differentiate between DRD1 and DRD5.…”
Section: Dopamine Alters Effectiveness Of Maraviroc In Hiv-infected Hmdmmentioning
confidence: 99%
See 2 more Smart Citations